تيمة البحر ودلالاتها ف رواية رقصة في الهواء الطلق لمرزاق بقطاش - غياط, حواء; عازب عثمان, نورة (جامعة الوادي - University of Eloued, 2023)
الملخص: لقد سعينا من خلال هذا البحث إلى دراسة تيمة البحر ودلالاتها في رواية مرزاق بقطاش وذلك باستخراج أبرز دلالات البحر والواردة في الرواية، كما تم التطرق للأماكن المفتوحة القريبة من البحر وعلاقتها بالبحر، كما يأخذ البحر دلالات متنوعة تختلف باختلاف النصوص السردية ، وقد وظف الراوي البحر لدلالته الواسعة ولمساهمته في تشكيل النسيج الروائي . الرواية تبدأ بجريمة قتل ، لخصت الواقع الاجتماعي المأساوي ، صورت مظاهر الفساد السائدة في المجتمع فترة الاستعمار Abstract : We have sought, through this research, to study the theme of the sea and its connotations in Marzak Baqtash's novel, by extracting the most prominent semantics of the sea in the novel. The open places near the sea and their relationship to the sea were also addressed. The sea also takes various connotations that differ according to the different narrative texts. The narrator used the sea for its significance. And his contribution to the formation of the novel fabric. The novel begins with a murder, summarizing the tragic social reality, and depicting the manifestations of corruption prevalent in society during the colonial period.
Keywords: تيمة البحر - رواية رقصة في الهواء الطلق - مرزاق بقطاش; the Theme of the Sea - A Dance in the Open Air - Merzak Baqtash